Preparation method of composite positive electrode material of vanadium pentoxide with three-dimensional microstructure and application of composite positive electrode material in zinc ion battery
By combining polyaniline and polypyrrole with vanadium pentoxide, a vanadium-based cathode structure with efficient migration channels is designed, which solves the cyclic stability and electron migration of vanadium oxide positive electrode materials, and significantly improves the battery capacity of aqueous zinc ion batteries and performance.
Patent Information
- Application Number
- CN202411458230.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The existing vanadium oxide positive electrode materials have problems such as poor cycling stability, low ion conductivity and slow electron migration in aqueous zinc ion batteries, which leads to rapid attenuation of battery capacity, limiting its application.
Using polyaniline (PANI) and polypyrrole (PPy) as organic polymers, the vanadium-based cathode stable framework structure with efficient migration channels is designed to optimize the structural stability of the material and zinc ions by composite with vanadium pentoxide (V2O5). Storage capability.
The structural stability and zinc ion storage capacity of the composite material are improved, the cycle stability and rate performance of the battery are significantly improved, and high specific capacity and excellent dynamic performance are achieved.
Smart Images

Figure HDA0005091090830000011 
Figure HDA0005091090830000012 
Figure HDA0005091090830000021
Abstract
Description
Technical field:
[0001] The invention belongs to the field of aqueous zinc ion batteries, and specifically relates to a preparation method and application of a composite positive electrode material of three-dimensional microstructure vanadium pentoxide. Background technology:
[0002] Aqueous zinc-ion batteries (AZIBs) are highly safe and low-cost secondary batteries, but the strong electrostatic interactions of the host materials and suboptimal cycle life have hindered the development of AZIBs. Therefore, the development of new cathode materials with stable structure, excellent capacity and high energy density will be an attractive research direction. Current research on cathode materials for AZIBs mainly focuses on manganese-based materials, vanadium-based compounds and Prussian blue analogs. Vanadium-based materials usually have high capacity and excellent rate performance due to the open framework crystal structure and multiple oxidation states of vanadium.
[0003] The most stable component in the vanadium oxide system is V2O5, and research on performance improvement is still ongoing. Although V2O5 has a series of advantages, it is subject to poor cycle stability, low ionic conductivity, slow Zn 2+ Diffusion and low electron content. To solve these problems, the research on vanadium-based materials has mainly focused on strategies to expand the interlayer spacing and optimize the interface to improve the cycle life and rate performance. However, the introduction of "lubricants" often causes the dissolution of vanadium-based materials, resulting in a significant reduction in battery capacity.
[0004] Existing studies have shown that the introduction of conductive materials such as carbon nanotubes, graphene and polymers into vanadium oxides can effectively improve the electrochemical performance of batteries. For example, CN202111662109.8 and CN202011069581.6 confirm that the introduction of PANI can improve the performance of batteries by increasing oxygen vacancies and optimizing interfaces. However, due to the slow electron migration path and the problem of vanadium dissolution, the rapid attenuation of battery capacity limits its further application.
[0005] How to further design a vanadium-based cathode stable skeleton structure with an efficient migration channel to improve the structural stability and zinc ion storage capacity of the composite material is to be solved by the present invention. Summary of the invention:
[0006] In order to solve the above problems, the present invention intends to prepare a ternary composite material of two organic polymers (polyaniline (PANI) and polypyrrole (PPy)) composited with vanadium pentoxide, and designs a vanadium-based cathode stable skeleton structure with an efficient migration channel to improve the structural stability and zinc ion storage capacity of the composite material.
[0007] The technical solution of the present invention is as follows:
[0008] The purpose of the present invention is to overcome the defects of the prior art and provide a method for preparing an organic polymer composite vanadium pentoxide material.
[0009] Another object of the present invention is to provide applications of two organic polymer composite vanadium pentoxide materials.
[0010] A method for preparing an organic polymer composite vanadium pentoxide material comprises the following steps:
[0011] (1) An inorganic vanadium source was dispersed in deionized water, polypyrrole was added and stirred in an oil bath (80°C) for 20 min, the solution was filtered and the precipitate was collected by vacuum filtration, washed several times with deionized water and anhydrous ethanol, and dried in vacuum at 60°C for 10 h.
[0012] (2) dispersing the dried material in step (1) in deionized water to obtain a dispersion, dissolving APS in an aqueous HCl solution to form a solution A, and magnetically stirring in an ice bath to achieve uniform dispersion; dispersing aniline monomer in an aqueous HCl solution to form a solution B, and stirring the solution in an ice bath to achieve uniform dispersion; adding solution B and solution A to the dispersion, stirring in an ice bath for 6 hours, centrifuging the obtained product three times with deionized water and ethanol, and drying in a vacuum oven at 60° C. for 10 hours.
[0013] (3) The above materials are further calcined in air at 100-300°C for 0.5-5h to further oxidize the vanadium ions and reduce the water content at a heating rate of 2°C min -1 , a ternary composite material of organic polymer (polyaniline, polypyrrole) and vanadium pentoxide is obtained;
[0014] Furthermore, the inorganic vanadium source compound in step (1) is selected from V2O5 and vanadate. The further preferred inorganic vanadium source compound is V2O5.
[0015] Furthermore, the mass ratio of the inorganic vanadium source compound to the polypyrrole is 2-5:0.5-1. The molar ratio of the inorganic vanadium source compound to aniline is 1-4:0.5-2; and the molar ratio of ammonium persulfate to aniline monomer is 1:1.
[0016] Furthermore, the concentration of hydrochloric acid is 0.01 to 1 mol / L. Further preferably, the concentration of hydrochloric acid synthesized in the organic polymer composite material is 0.02 mol / L.
[0017] Furthermore, the ice bath condition refers to controlling the reaction temperature at 0-5°C.
[0018] Further, as a preference, the calcination temperature of the inorganic vanadium compound precursor and the organic polymer is 200°C, the calcination time is 2h, and the heating rate is 2°C·min -1 .
[0019] The organic polymer composite vanadium pentoxide material prepared by the preparation method is used in the positive electrode of zinc ion battery.
[0020] Embedding polypyrrole into the main material can not only expand the interlayer spacing, but also improve the conductivity of the mixed cathode. In addition, the introduction of the synergistic PANI chain provides more zinc storage sites. Polyaniline reacts in situ on the prepared vanadium-based material-polypyrrole material to generate 3D amorphous nanofibers. These nanofibers are randomly stacked to form an open interpenetrating network structure, providing a stable channel for zinc ion migration, optimizing the interface of the composite material, and providing a more effective ion migration pathway and a complete structure.
[0021] The beneficial effects of the present invention are:
[0022] 1. The organic polymer composite vanadium pentoxide material prepared by the present invention can combine the advantages of inorganic vanadium oxide and organic polymer at the same time, and has a simple preparation process and low cost.
[0023] 2. The specific organic polymers in the present invention can not only form hydrogen bonds with the vanadium oxide skeleton to maintain the structural stability of the material; these organic polymers can also better expand the interlayer spacing of vanadium pentoxide, improve the zinc ion insertion and extraction kinetics, and thus obtain excellent cycle stability and rate performance.
[0024] 3. The organic polymer polyaniline in the present invention has its own active sites and can also participate in the storage process of zinc ions, providing a certain capacity to avoid the theoretical capacity of the material being reduced due to metal ions occupying the reaction sites, thereby making the vanadium pentoxide material have a high specific capacity. The in-situ polymerization of polyaniline on the vanadium-based-polypyrrole material produces 3D amorphous nanofibers with a diameter of about 200nm. These nanofibers are randomly stacked to form an open interpenetrating network structure, providing a stable channel for the migration of zinc ions. The composite sample presents a rough surface and irregular distribution.
[0025] 4. The organic polymer introduced in the present invention has high conductivity, and the prepared ternary composite material exhibits excellent dynamic properties. Description of the drawings:
[0026] Figure 1 These are the XRD diagrams of Example 1, Example 2, Example 3, polyaniline, and polypyrrole polymers in the present invention.
[0027] Figure 2 These are SEM images of Example 1 and Example 3 of the present invention.
[0028] Figure 3 This is a low-magnification SEM photograph of Example 3 of the present invention.
[0029] Figure 4 This is a zinc storage rate performance diagram of Example 1, Example 2, and Example 3 of the present invention.
[0030] Figure 5 For example, in Example 1, Example 2, and Example 3 of the present invention, the temperature is 0.5A·g -1 Zinc storage cycle performance diagram under current density.
[0031] Figure 6 This is a high current cycle performance diagram of Example 3 in the present invention.
[0032] Figure 7 The present invention is Example 4 at 0.5A·g -1 Zinc storage cycle performance diagram under current density.
[0033] Figure 8 The present invention is Example 5 at 0.5A·g -1 Zinc storage cycle performance diagram under current density.
[0034] Fig. 9 The comparative example 1 in the present invention is 0.5A·g -1 Zinc storage cycle performance diagram under current density.
[0035] Fig.10 The comparative example 2 in the present invention is 0.5A·g -1 Zinc storage cycle performance diagram under current density.
[0036] Fig.11 The comparative example 3 in the present invention is 0.5A·g -1 Zinc storage cycle performance diagram under current density.
[0037] Fig.12 The comparative example 4 of the present invention is 0.5A·g -1 Zinc storage cycle performance diagram under current density.
[0038] Fig.13 The comparative example 5 in the present invention is 0.5A·g -1 Zinc storage cycle performance diagram under current density. Specific implementation method:
[0039] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0040] Embodiment 1:
[0041] Example 1 directly uses vanadium pentoxide produced by MacLean, calculated as VO.
[0042] Embodiment 2:
[0043] (1) 80 mg of polypyrrole was added to a solution containing 363 mg (2 mmol) of vanadium oxide precursor (V2O5) dispersed in deionized water, and the mixture was stirred thoroughly at 80° C. The obtained product was washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours.
[0044] (2) The above materials were further calcined in air at 200 °C for 2 h at a heating rate of 2 °C min -1 , to further oxidize the vanadium ions and reduce the water content to obtain the binary composite material PVO.
[0045] Embodiment 3:
[0046] (1) 80 mg of polypyrrole was added to a solution containing 2 mmol of vanadium oxide precursor (V2O5) dispersed in deionized water, and the mixture was stirred completely at 80° C. The obtained product was washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours to obtain the product PVO.
[0047] (2) Then disperse the above-mentioned product PVO in deionized water to obtain a PVO dispersion. Dissolve 0.5 mmol APS in 0.02 mol·L -1 HCl aqueous solution to form solution A. Magnetic stirring was performed in an ice bath to achieve uniform dispersion. 0.5 mmol aniline monomer was dispersed in 0.02 mol·L -1 Solution B was formed in the HCl aqueous solution and stirred in an ice bath for 10 minutes. Solution B and solution A were added to the PVO dispersion and stirred in an ice bath for 6 hours. The obtained product was centrifuged three times with deionized water and ethanol and dried in a vacuum oven at 60°C for 10 hours.
[0048] (3) The above materials were further calcined in air at 200 °C for 2 h at a heating rate of 2 °C min -1 , to further oxidize the vanadium ions and reduce the water content, to obtain the ternary composite material PPVO. Example 4:
[0049] (1) 2 mmol of vanadium oxide precursor (V2O5) was dispersed in 20 mL of ionized water, 114 mg (0.5 mmol) of ammonium persulfate (APS) and 46 mg (0.5 mmol) of aniline were dissolved in 0.02 mol / L hydrochloric acid respectively and then added to the vanadium oxide precursor dispersion, stirred for 24 h in an ice bath, then washed with water, centrifuged three times, and dried in a vacuum oven at 60 ° C for 10 hours to obtain a product of a polyaniline and vanadium pentoxide complex;
[0050] (2) The above materials are further calcined in air at 200°C for 2 h with a heating rate of 2°C·min-1 to further oxidize the vanadium ions and reduce the water content to obtain a binary composite material PVO.
[0051] Embodiment 5:
[0052] (1) 2 mmol of vanadium oxide precursor (V2O5) was dispersed in 10 mL of ionized water, 0.5 mmol of ammonium persulfate (APS) and 0.5 mmol of aniline were dissolved in 0.02 mol / L hydrochloric acid respectively and then added to the vanadium oxide precursor dispersion, stirred for 24 h in an ice bath, then washed with water, centrifuged three times, and dried in a vacuum oven at 60°C for 10 h to obtain a product of a polyaniline and vanadium pentoxide complex;
[0053] (2) The product of step (1) was completely dispersed in deionized water, and 80 mg of polypyrrole was added and stirred at 80° C. The obtained product was washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours.
[0054] (3) The dried material was further calcined in air at 200 °C for 2 h at a heating rate of 2 °C min -1 , to further oxidize the vanadium ions and reduce the water content to obtain the ternary composite material 2-PPVO.
[0055] Comparative Example 1
[0056] (1) First, 80 mg of polypyrrole was added to deionized water in which 2 mmol of zinc vanadate was dispersed, and the mixture was stirred completely at 80° C. The obtained product was washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours to obtain a composite of zinc vanadate and polypyrrole.
[0057] (2) Then disperse the product of step (1) in deionized water and dissolve 0.5 mmol APS in 0.02 mol·L -1 In a hydrochloric acid aqueous solution, solution A was formed. Magnetic stirring was performed in an ice bath to achieve uniform dispersion. 0.5 mmol aniline monomer was dispersed in 0.02 mol·L -1 Solution B is formed in the HCl aqueous solution and stirred in an ice bath for 10 minutes. Solution B is quickly added to solution A and stirred in an ice bath for 6 hours. The resulting product is centrifuged three times with deionized water and ethanol and dried in a vacuum oven at 60°C for 10 hours to obtain a ternary complex of zinc vanadate.
[0058] (3) The above materials were further calcined in air at 200 °C for 2 h at a heating rate of 2 °C min -1 , to reduce the water content and obtain the final composite material PPVO.
[0059] Comparative Example 2:
[0060] (1) First, 80 mg of polypyrrole was added to deionized water containing 1 mmol of vanadium oxide precursor, and the mixture was stirred at 80° C. The obtained product was washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours to obtain the product PVO.
[0061] (2) Then disperse the product PVO in deionized water to obtain a PVO dispersion. Dissolve 0.5 mmol APS in 0.02 mol·L -1 In a hydrochloric acid aqueous solution, solution A was formed. Magnetic stirring was performed in an ice bath to achieve uniform dispersion. 0.5 mmol aniline monomer was dispersed in 0.02 mol·L -1 Solution B was formed in the HCl aqueous solution and stirred in an ice bath for 10 minutes. Solution B and solution A were added to the PVO dispersion and stirred in an ice bath for 6 hours. The obtained product was centrifuged three times with deionized water and ethanol and dried in a vacuum oven at 60°C for 10 hours to obtain the product PPVO.
[0062] (3) The above materials were further calcined in air at 200 °C for 2 h at a heating rate of 2 °C min -1 , to further oxidize the vanadium ions and reduce the water content to obtain the final composite material PPVO.
[0063] Comparative Example 3:
[0064] (1) Add 30 mg of polyethylene to a solution containing 2 mmol of vanadium oxide precursor dispersed in deionized water, and stir completely at room temperature for 8 hours. The obtained product is washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours to obtain a composite of polyethylene and vanadium pentoxide.
[0065] (2) The above materials were further calcined in air at 200 °C for 2 h at a heating rate of 2 °C min -1 , to further oxidize the vanadium ions while reducing the water content to obtain a composite material of vanadium oxide and polyethylene.
[0066] Comparative Example 4
[0067] (1) First, 2 mmol of vanadium oxide precursor was dispersed in deionized water, 80 mg of polypyrrole was added, and the mixture was stirred completely at 80° C. The obtained product was washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours to obtain the product PVO.
[0068] (2) Then disperse the product PVO in deionized water to obtain a PVO dispersion. Dissolve 0.5 mmol APS in 0.05 mol·L-1 In a hydrochloric acid aqueous solution, solution A was formed. Magnetic stirring was performed in an ice bath to achieve uniform dispersion. 0.5 mmol aniline monomer was dispersed in 0.05 mol·L -1 Solution B was formed in the HCl aqueous solution and stirred in an ice bath for 10 minutes. Solution B and solution A were added to the PVO dispersion and stirred in an ice bath for 6 hours. The obtained product was centrifuged three times with deionized water and ethanol and dried in a vacuum oven at 60°C for 10 hours to obtain the product PPVO.
[0069] (3) The above materials were further calcined in air at 200 °C for 2 h at a heating rate of 2 °C min -1 , to further oxidize the vanadium ions and reduce the water content to obtain the final composite material PPVO.
[0070] Comparative Example 5
[0071] (1) First, 2 mmol of vanadium oxide precursor was dispersed in deionized water, 80 mg of polypyrrole was added, and the mixture was stirred at 80° C. The obtained product was washed three times with deionized water and ethanol, and dried in a vacuum oven at 60° C. for 10 hours to obtain the product PVO.
[0072] (2) Then disperse the product PVO in deionized water to obtain a PVO dispersion. Dissolve 0.5 mmol APS in 0.02 mol·L -1 In a hydrochloric acid aqueous solution, solution A was formed. Magnetic stirring was performed in an ice bath to achieve uniform dispersion. 0.5 mmol aniline monomer was dispersed in 0.02 mol·L -1 Solution B was formed in the HCl aqueous solution and stirred in an ice bath for 10 minutes. Solution B and solution A were added to the PVO dispersion and stirred in an ice bath for 6 hours. The obtained product was centrifuged three times with deionized water and ethanol and dried in a vacuum oven at 60°C for 10 hours to obtain the product PPVO.
[0073] (3) The above materials were further calcined in air at 350 °C for 2 h at a heating rate of 2 °C min -1 , to further oxidize the vanadium ions and reduce the water content to obtain the final composite material PPVO.
[0074] The products obtained in the above examples and comparative examples are applied to positive electrode materials of batteries, as follows: (1) Preparation of electrolyte
[0075] Electrolyte for zinc ion storage: deionized water as solvent, zinc trifluoromethanesulfonate as zinc salt, 3 mol·L -1 The electrolyte is used for storage of zinc ions in zinc ion battery assembly.
[0076] (2) Preparation of positive electrode sheet
[0077] The organic polymer composite vanadium pentoxide positive electrode active material, the conductive agent acetylene black, and the PVDF binder were mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone was added and stirred to obtain a slurry. The slurry was evenly coated on a stainless steel mesh and placed in a vacuum drying oven at 60°C for 10 hours.
[0078] (3) Preparation of batteries
[0079] The positive electrode sheet, negative electrode sheet, glass fiber separator, gasket and electrolyte were assembled into a CR2016 button battery, the battery was sealed, and the electrochemical performance test was performed after standing for 2 hours.
[0080] The experimental results of the above embodiments and comparative examples are as follows:
[0081] Figure 1 The XRD spectra of five samples in Example 1, Example 2, Example 3, polypyrrole, and polyaniline 5. It can be seen from the analysis of the figure that PPy is a random polymer molecule, the molecular chain has no crystallinity, and there is only one amorphous broad peak on the XRD curve. Compared with the original VO, the crystallinity of the composite PVO is lower. Since the final product PPVO is calcined, part of the water and organic matter in the sample are removed, and the crystallinity is improved. And it is consistent with the diffraction peak position in the standard card of VO (JCPDS 41-1426), proving that the structure of VO is not destroyed or covered during the composite process.
[0082] Figure 2 200 nm SEM photos of two samples of organic polymer composite vanadium pentoxide (PPVO) prepared in Example 3 and vanadium pentoxide in Example 1. From the analysis of the figure, it can be seen that the vanadium pentoxide sample without composite organic polymer has a nanorod structure of 1 micron in length and about 50 nanometers in width. Example 3 Due to the incorporation of multiple polymers, the in-situ polymerization of polyaniline on the vanadium-based material produces 3D amorphous nanofibers with a diameter of about 200 nm. These nanofibers are randomly stacked to form an open interpenetrating network structure, providing a stable channel for zinc ion migration. The composite sample presents a rough surface and irregular distribution.
[0083] Figure 3 This is a 2 micron SEM photo of the organic polymer composite vanadium pentoxide (PPVO) prepared in Example 3. As can be seen from the figure, the composite vanadium pentoxide presents clusters of different sized spheres with irregular distribution.
[0084] Figure 4 The rate performance diagrams of the samples of Example 1, Example 2, and Example 3 are shown in Figure 1. The PPVO of Example 3 is at 0.1 A·g -1 The specific capacity at the current density is 466.5 mAh g-1 , increased to 5A·g -1 The current density specific capacity is 196.7 mAh g -1 When the current density returns to 0.1A·g -1 The current density and specific capacity show no attenuation, and the reversible capacity can still be maintained at 481.3 mAh g -1 The PVO of Example 2 is 0.1A·g -1 The specific capacity at the current density is 275.5 mAh g -1 , increased to 5A·g -1 The current density specific capacity is 94.7 mAh g -1 When the current density returns to 0.1A·g -1 The current density and reversible capacity can still be maintained at 325.3 mAh g -1 It has excellent rate performance, but due to the certain mass proportion of PPy, the specific capacity is slightly lower. -1 The specific capacity at the current density is 321.5 mAh g -1 , increased to 5A g -1 The current density specific capacity is 146.7 mAh g -1 When the current density returns to 0.1A·g -1 The current density and reversible capacity can still be maintained at 288.3 mAh g -1 The specific capacity has obviously decayed and returned to 0.1A·g -1 By comparison, it can be proved that PPVO has excellent tolerance and high specific capacity.
[0085] Figure 5 The zinc storage cycle performance diagram of the samples of Example 1, Example 2, and Example 3. As can be seen from the figure, the cycle performance and reversible capacity of the PPVO of Example 3 are significantly improved. -1 At the current density, after 500 cycles, the reversible capacity can be maintained at 372.5 mAh g -1 The capacity retention rate is 86.7%, and the capacity retention rate and zinc ion storage efficiency are significantly higher than those of the other two samples. At the same time, the cycle performance of PVO in Example 2 is also improved to a certain extent. -1 At the current density, after 500 cycles, the reversible capacity can be maintained at 285.5 mAh g -1 , the capacity retention rate is 66.7%. VO has an ultra-high initial capacity, but at 0.5A·g -1 At this current density, after 500 cycles, the reversible capacity is only 205.5 mAh g -1, the capacity retention rate is 40.7%. By comparison, it can be proved that PPVO has excellent cycle performance, which is due to its optimized structure and enhanced conductivity.
[0086] Figure 6 This is the cycling performance diagram of the PPVO prepared in Example 3 at a high current density. -1 At the current density, after 3000 cycles, the reversible capacity can be maintained at 288.5 mAh g -1 , the capacity retention rate is 87.7%.
[0087] Figure 7 For Example 4 at 0.5A·g -1 Cyclic performance diagram under current density, the initial specific capacity can reach up to 484.1mAh·g -1 After 500 cycles, the reversible capacity is 355.3 mAh g -1 The capacity retention rate is 73.4%, and the coulombic efficiency fluctuates greatly during the cycle. This proves that the addition of PANI has little effect on the theoretical specific capacity of the positive electrode material, but the cycle stability needs to be improved.
[0088] Figure 8 Example 5 at 0.5A·g -1 Cyclic performance diagram under current density, the specific capacity can reach up to 308.9 mAh g -1 After 500 cycles, the reversible capacity is 209.6 mAh g -1 The capacity retention rate is 59.4%. We speculate that the rapid decrease in capacity is due to the fact that the structure of polyaniline is destroyed during the heating process of the subsequent composite polypyrrole when polyaniline is first composited.
[0089] Fig. 9 For comparative example 1 at 0.5A·g -1 Cyclic performance diagram under current density. Due to the low theoretical specific capacity and unstable structure of zinc vanadate, the initial specific capacity can reach up to 318.7 mAh g -1 After 500 cycles, the reversible capacity is 189.6 mAh g -1 , the capacity retention rate is 67.8%.
[0090] Fig.10 For comparative example 2 at 0.5A·g -1 Cycling performance diagram at current density, initial capacity 62.7 mAh g -1 After 500 cycles, the reversible capacity is 56.1 mAh g -1 , which shows a low specific capacity. The low specific capacity is caused by the low content of active substances.
[0091] Fig.11 For comparative example 3 at 0.5A·g -1 Cyclic performance diagram under current density. Due to the low conductivity of the polymer, the battery specific capacity can reach up to 330.4 mAh g -1 The battery was damaged after 145 cycles.
[0092] Fig.12 For comparative example 4 at 0.5A·g -1 Cyclic performance diagram under current density, the specific capacity can reach up to 401.4mAh·g -1 After 500 cycles, the reversible capacity is 285.6 mAh g -1 The capacity retention rate is 71.1%. The preparation process of polyaniline requires hydrochloric acid, but the structure of vanadium-based materials is easily destroyed under acidic conditions, so the concentration of hydrochloric acid needs to be controlled. -1 The positive electrode prepared under hydrochloric acid aqueous solution conditions has a relatively high initial capacity, but the capacity retention rate needs to be improved.
[0093] Fig.13 For comparative example 5 at 0.5A·g -1 Cyclic performance diagram under current density, the specific capacity can reach up to 367.2mAh·g -1 After 500 cycles, the reversible capacity is 245.3 mAh g -1 , the capacity retention rate is 66.7%. Because the temperature is too high, the organic matter will be burned, resulting in structural instability and lower capacity retention rate.
[0094] This patent invents a PPVO composite electrode with a three-dimensional skeleton structure, which improves the low conductivity and solubility of vanadium pentoxide by introducing highly conductive organic polymers PPy and PANI as the main supporting materials. 2+ The optimized PPVO has a high specific capacity (at 0.5Ag -1 The following is 442.9mAh·g -1 ), excellent rate performance, at 3A·g -1 The capacity retention rate is 87.7% after 3000 cycles.
Claims
1. A method for preparing a composite positive electrode material of three-dimensional microstructure vanadium pentoxide, characterized in that: The preparation steps are as follows: (1) dispersing an inorganic vanadium source in deionized water, adding polypyrrole and stirring under heating conditions, filtering after stirring, collecting the precipitate, washing it with distilled water and anhydrous ethanol for several times, and vacuum drying; (2) dispersing the above-mentioned dried product in deionized water to obtain a dispersion, dissolving ammonium persulfate in an aqueous hydrochloric acid solution, and stirring in an ice bath to form a solution A; Dispersing aniline monomer in a hydrochloric acid aqueous solution, stirring evenly in an ice bath to form a solution B; adding solution B and solution A to the dispersion, stirring in an ice bath to react, and after the reaction, centrifuging and drying the reaction product; (3) calcining the dried product obtained in step (2) in air at 100 to 300° C. for 0.5 to 5 h to obtain a composite positive electrode material having a three-dimensional microstructure of vanadium pentoxide.
2. The method for preparing the composite positive electrode material of three-dimensional microstructure vanadium pentoxide according to claim 1, characterized in that: In step (1), the inorganic vanadium source is selected from V2O5 and vanadate; the mass ratio of the inorganic vanadium source compound to the polypyrrole is 2-5:0.5-1.
3. The method for preparing the composite positive electrode material of three-dimensional microstructure vanadium pentoxide according to claim 1, characterized in that: The molar ratio of the inorganic vanadium source compound to aniline is 1-4:0.5-2; the molar ratio of ammonium persulfate to aniline monomer is 1:
1.
4. The method for preparing the composite positive electrode material of three-dimensional microstructure vanadium pentoxide according to claim 1, characterized in that: The concentration of the hydrochloric acid aqueous solution in step (2) is 0.01 to 1 mol / L.
5. The method for preparing the composite positive electrode material of three-dimensional microstructure vanadium pentoxide according to claim 4, characterized in that: The concentration of the hydrochloric acid aqueous solution in step (2) is 0.02 mol / L.
6. The method for preparing the composite positive electrode material of three-dimensional microstructure vanadium pentoxide according to claim 1, characterized in that: Step (3) The calcination temperature is 200°C, the calcination time is 2h, and the heating rate is 2°C·min -1 .
7. A composite positive electrode material of three-dimensional microstructured vanadium pentoxide prepared according to the method according to any one of claims 1 to 6.
8. Use of the composite positive electrode material of three-dimensional microstructure vanadium pentoxide prepared by the method according to any one of claims 1 to 6 in zinc ion batteries.
Citation Information
Patent Citations
A vanadium pentoxide cathode material, its preparation method and application
CN112054160B
Polyaniline modified vanadium pentoxide nanosheet material as well as preparation method and application thereof
CN114530599A
Battery anode material and preparation method thereof
CN109494369A
Polyaniline in-situ polymerization intercalated vanadium pentoxide and preparation method and application thereof
CN111847510A
Preparation method of organic-inorganic hybrid material based on vanadium pentoxide and application of organic-inorganic hybrid material in zinc ion battery
CN112993217A